Ալևիական կազմակերպությունների հիմնումը և գործունեությունը Եվրոպայում 1960-2000-ական թթ. - Հարությունյան, Վարդան («Զանգակ - 97»)
The Alevi community was opened for the others after the beginning of the urbanization process in Turkey in 1960s. Many Alevis left their families seeking for job not only in the big cities of Turkey, but in European countries also. Many of them immigrated to Germany and after some years began organizing Alevi unions. During two decades many Alevi organizations emerged and were combined in Federation of Alevi Unions, which was renamed Confederation of Alevi Unions of Europe lately. This organization played a great role in the life of Alevis living in Europe and in the political life of Alevis living in Turkey. Becoming more and more active in Europe Alevis organized demonstrations in the big cities and presented their demands about recognizing their religious identity by European countries and especially by Turkey. The Alevi organizations in Europe aim to help Turkey in the process of integration in European Union.
Keywords: Պատմություն